Literatur in Österreich 1938-1945, Oberösterreich Handbuch eines literarischen Systems - Gradwohl-Schlacher, Karin (2014)
Dictionary of a province during the National Socialist era ("Oberdonau"), understood as a regional literary subsystem described in terms of the interaction of authors and literary institutions